Peran Mediasi Value Perceived by Employee dan Perceived HR Service Quality atas Pengaruh Harapan Karyawan terhadap Kepuasan Kerja Karyawan - Reni Rifatun Novita; Widiya Dewi Anjaningrum (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This research is a field on casual daily employees of the production division of PT. Gatra Mapan, Tbk. This has the main objective of proving the existence of a mediating function of Value Perceived by Employee, and Perceived HR Service Quality on the influence of employee expectations on employee job satisfaction. Data collection on 116 employees was conducted through a questionnaire instrument. The data obtained were analyzed through the outer and inner model and hypothesis testing in PLS analysis. The results of this study indicate that Perceived Value by Employee, and Perceived HR Service Quality are proven to be mediators between employee expectations and employee job satisfaction.Employee expectations can create perceptions about the value and quality of HR services that are felt by employees at work. Therefore, employees can feel job satisfaction which has an impact on the quality of their work so that they can beneficial for industrial development. Future research is expected to reveal whether employees who are satisfied at work will affect their creativity andtheir product quality.